2021
DOI: 10.1177/02537176211033643
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Autopsy Studies of Suicide in South East Asia

Abstract: Background: Psychiatric disorders have been identified as an important risk factor for suicide. However, different psychological autopsy studies have revealed different prevalences at different times and places. Objective: We aimed to see the distribution of psychological autopsy studies and the prevalence of mental disorders among suicides and identify major risk factors in Southeast Asian countries. Method: We scrutinized psychological autopsy studies published in the World Health Organization (WHO) South-Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…9 Chandrasekaran and Gnanaselane (2008) investigated the predictors of repeated suicide attempts of 348 samples from India and found that repeat suicide attempts are associated with depression, hopelessness and suicidal intent, and presence of major depression and social dissidence are predictive factors for repeat attempts. 10 A recent scoping review by Arafat et al (2022) revealed that the prevalence of depression among fatal (37.3%) and nonfatal suicidal attempts (32.7%) in South Asian countries seems to be lower compared to other regions of the world. 11 In another research, Arafat et al found that the presence of preexisting psychiatric morbidities and stressful life events are the most common risk factors for suicide in South Asia.…”
Section: Suicide In South East Asiamentioning
confidence: 99%
See 2 more Smart Citations
“…9 Chandrasekaran and Gnanaselane (2008) investigated the predictors of repeated suicide attempts of 348 samples from India and found that repeat suicide attempts are associated with depression, hopelessness and suicidal intent, and presence of major depression and social dissidence are predictive factors for repeat attempts. 10 A recent scoping review by Arafat et al (2022) revealed that the prevalence of depression among fatal (37.3%) and nonfatal suicidal attempts (32.7%) in South Asian countries seems to be lower compared to other regions of the world. 11 In another research, Arafat et al found that the presence of preexisting psychiatric morbidities and stressful life events are the most common risk factors for suicide in South Asia.…”
Section: Suicide In South East Asiamentioning
confidence: 99%
“…11 In another research, Arafat et al found that the presence of preexisting psychiatric morbidities and stressful life events are the most common risk factors for suicide in South Asia. 12…”
Section: Suicide In South East Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…These findings concur with reports from Asian settings where life events and interpersonal conflicts have been noted to be major drivers of suicide, unlike the West where psychiatric morbidity remains the principal risk factor. 8,10,19,44 Previous studies from Turkey, a transcontinental country located both in Asia and in Europe, have shown the key role of stressful life events and poor social support in triggering suicidal behavior across age groups. 45,46 Our findings imply that suicide prevention efforts in Muslim nations must also focus adequately on the social determinants of suicide, apart from addressing barriers to seeking mental health services, to effectively tackle the menace of suicide.…”
Section: Risk Factors For Suicide In Muslim Countriesmentioning
confidence: 99%
“…As a result, any risk factor with a specific cause–effect association with suicide is difficult to identify [ 3 ]. Although psychiatric disorders have been identified as important risk factors for suicide consistently, the rate varies between Western countries and LMICs as studies from the former report rates around 90% whilst the LMICs show a much lower rate of mental disorders among suicides [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%